Administration of Testosterone and its Rationale in the Treatment of Erectile Dysfunction (Anwer Khan Modern Medical College Journal, 2017)
Background: Despite increasing use of testosterone in the management erectile dysfunction, debate remains regarding the selection of candidate for the hormonal treatment. The aim of this study is to find out the role of testosterone in erectile dysfunction (ED), the incidence of testosterone deficiency in the patient of ED and therapeutic response of testosterone in ED in common practice.Material & Methods: This cross-sectional study had conducted among the patients with age above 30 years, complaining of erectile dysfunction treated with testosterone by self-medication or clinical practitioners. Total 103 cases interviewed, who attended the private chamber of Urologists and the Urology OPD, BIRDEM General Hospital between periods of April 2014 to September 2015.Result: Of 103 cases, testosterone level was normal in 78.6% cases. All were treated with testosterone. Among the participants 47.57% were between 30-40 years and 9.09% were of the age between 60-70 years. Twenty-two patients having testosterone deficit were treated with testosterone supplement and marked improvement was observed (88.1%). In this study 49 patients having normal testosterone level received testosterone along with sildenafil or tadalafil, of these 47 cases (95%) had moderate to marked improvement. On the other hand 32 patients having normal testosterone level received testosterone monotherapy but there was no improvement in 87.5% cases.Conclusion: The result of the study suggests that testosterone replacement therapy is beneficial in patient of ED due to hypogonadism. However, testosterone monotherapy in erectile dysfunction with normal testosterone level should be considered injudicious.Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 45-49